A Heparin-coated Circuit Maintains Platelet Aggregability in Response to Shear Stress in an In Vitro Model of Cardiopulmonary Bypass - Hioki, I.; Nishikawa, M.; Onoda, K.; Shimono, T.; Shimpo, H.; Tanaka, K.; Suzuki, Y.; Shiku, H.; Ikeda, Y.; Yada, I. (Thrombosis and Haemostasis, 1998)
Alterations in platelet aggregability may play a role in the pathogenesis of qualitative platelet defects associated with cardiopulmonary bypass (CPB). We circulated fresh heparinized whole blood through tubing sets coated with heparin (C group, n = 10) and through non-coated sets (N group, n = 10) as a simulated CPB circuit. Shear stress (108 dyne/cm2)-induced platelet aggregation (hSIPA), plasma von Willebrand factor (vWF) activity and platelet glycoprotein (GP) Ib expression were measured, before, during, and after this in vitro set up of circulation. In the two groups, the extent of hSIPA significantly decreased during circulation and was partially restored after circulation. Decreases in the extent of hSIPA were significantly less with use of heparin-coated circuits. There was an equivalent reduction in plasma vWF activity, in the two groups. Expression of platelet surface GP Ib decreased significantly during circulation and recovered after circulation. Reduction of surface GP Ib expression during circulation was significantly less in the C group than that in the N group. Decrease in surface GP Ib expression correlated (r = 0.88 in either group) with the magnitude of hSIPA, in the two groups. The progressive removal of surface GP Ib was mainly attributed to redistribution of GP Ib from the membrane skeleton into the cytoskeleton. Our observations suggest that use of heparin-coated circuits partly blocks the reduction of hSIPA, as a result of a lesser degree of redistribution of GP Ib.